ANALISIS FUNDAMENTAL DAN EKSPLORASI KOMPREHENSIF MANAJEMEN RISIKO KREDIT PADA PROGRAM KPR SUBSIDI DI PT. BANK TABUNGAN NEGARA (PERSERO) Tbk. KANTOR CABANG JAMBI: SEBUAH KAJIAN TEORITIS DAN PRAKTIS DALAM MENJAGA STABILITAS KEUANGAN PERBANKAN - Silalahi, Arlis Futri; Dahlia, Dahlia (Jurusan Akuntansi FEB Universitas Jambi, 2025)
This extensive scientific work explores every dimension of the credit risk management procedures implemented by Bank BTN Jambi Branch Office in facilitating housing needs for Low-Income Communities (MBR). Within an economic landscape fraught with uncertainty, credit risk emerges as an existential challenge for the banking industry. This research employs a qualitative-phenomenological methodology to dissect how internal bank policies interact with customer behavior in Jambi Province. The analysis spans from the highly selective pre-screening phase via SLIK OJK and multi-layered repayment capacity verification to educational and persuasive non-performing loan handling strategies. The research findings provide new insights into the importance of synchronizing digital technology with physical field verification in suppressing Non-Performing Loan (NPL) rates.